2010
DOI: 10.1136/jnnp.2010.215681
|View full text |Cite
|
Sign up to set email alerts
|

Rest tremor in advanced essential tremor: a post-mortem study of nine cases

Abstract: In nine ET brains with upper-extremity rest tremor, neither Lewy body-containing neurons nor Lewy neurites were found on α-synuclein immunostained sections, and other pathological changes in the basal ganglia were minimal. These data support the notion that isolated rest tremor in longstanding ET is not the expression of underlying Lewy body pathology in the SNc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 30 publications
2
49
0
2
Order By: Relevance
“…We have shown previously that the presence of isolated rest tremor (i.e., in the absence of other features of parkinsonism) in advanced ET is not an indicator of the presence or emergence of Lewy body pathology in these cases [16]. Nonetheless, the emergence of rest tremor in some cases, particularly if accompanied by bradykinesia or rigidity, may be an early manifestation of emerging Lewy body disease.…”
Section: Discussionmentioning
confidence: 97%
“…We have shown previously that the presence of isolated rest tremor (i.e., in the absence of other features of parkinsonism) in advanced ET is not an indicator of the presence or emergence of Lewy body pathology in these cases [16]. Nonetheless, the emergence of rest tremor in some cases, particularly if accompanied by bradykinesia or rigidity, may be an early manifestation of emerging Lewy body disease.…”
Section: Discussionmentioning
confidence: 97%
“…ET cases with rest tremor also had more severe postural and kinetic tremor and were more likely to have head tremor than those without rest tremor [13]. Another study of nine ET cases with rest tremor reported a median disease duration of 42 years [15]. All cases had moderate to severe action tremor of the arms and cranial (head, jaw or voice) tremor [15].…”
Section: Bedside Examination: Distinguishing Et From Pdmentioning
confidence: 99%
“…Another study of nine ET cases with rest tremor reported a median disease duration of 42 years [15]. All cases had moderate to severe action tremor of the arms and cranial (head, jaw or voice) tremor [15]. Rest tremor was bilateral in seven cases, and in five cases, the side with more severe rest tremor was concordant with the side with more severe action tremor [15].…”
Section: Bedside Examination: Distinguishing Et From Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…In one tertiary referral center, the patients with rest tremor had kinetic tremor that was more severe, more disseminated, and of longer duration than ET patients without rest tremor 69. Although the pathogenesis of rest tremor in ET is unknown,70 it could be related to pathologic spreading to extracerebellar circuits in patients with severe, long-standing, and disseminated disease. Alternatively, it may result from a pathological interaction between the basal ganglia and the cerebello-thalamo-cortical circuits 71…”
Section: The Neurodegenerative Modelmentioning
confidence: 99%